A systematic review of the evolution of GPS use in active living research: A state of the evidence for research, policy, and practice. (November 2020) - Katapally, Tarun R.; Bhawra, Jasmin; Patel, Pinal
Abstract: This is the first systematic review to comprehensively capture Global Positioning Systems' (GPS) utilization in active living research by investigating the influence of physical contexts and social environment on all intensities of physical activity and sedentary behavior among all age groups. An extensive search of peer-reviewed literature was conducted using six databases. Out of 2026 articles identified, 129 studies met the inclusion criteria. After describing the evolution of GPS use across four themes (study designs and methods, physical contexts and social environment, active transportation, and behaviors), evidence-based recommendations for active living research, policy, and practice were generated. Highlights: First systematic review to comprehensively explore the evolution of GPS use in active living research. A state of the evidence article with recommendations for active living research, policy, and practice. Investigated the influence of multiple physical contexts and social environment on both physical activity and sedentary behavior in all age groups. Future directions point toward the utilization of GPS in citizen-owned smartphones to advance active living research, policy and practice.